Regional innovation ecosystems and smart specialization: opportunities and challenges for regions - Lopes, João (2021)
Global competition is today a reality and making smart regions smarter through smart specialization is currently on the political and economic agenda of territories. This study aims to contribute to clarifying the framework for the regional innovation ecosystems as well as identifying new research paths. Through extensive research using the Web of Science database with resource to a bibliometric analysis on smart specialization, six clusters were identified: cluster 1 – innovation networks and triple helix; cluster 2 - regional innovation systems; cluster 3 – regional innovation network; cluster 4 - smart innovation policies; cluster 5 – smart specialization; and cluster 6 - Asian innovation systems. Several future lines of research recently published in literature distributed by the six clusters were identified. This study also contributes to open new research horizons in these areas of knowledge, allowing the emergence of new streams of thought on the part of scholars, policymakers, economic agents and society in general.